Positive versus negative incentives for loan repayment in microfinance: A game theory approach. Issue 2 (14th November 2018) - Brihaye, Thomas; Pril, Julie De; Labie, Marc; Périlleux, Anaïs
Abstract: In most of the methodologies used so far by microfinance institutions, negative incentives are predominant, which can contrast with these institutions' social mission. This paper investigates whether the microfinance industry could benefit from using more positive incentives. The main results of our game model are twofold. First, (positive or negative) incentives increase "on‐time" repayments. Second, the client is more likely to repay her loan with the encouragement of a bonus scheme rather than under the pressure of a sanction, regardless of the amount. This paper therefore argues for the increased use of positive incentives in the industry.